Decision of using local supplier as a CSR strategy: drivers and benefits for large international companies - Luca, Giovanna Maria Lamberti de (2014)
This research provides a comprehensive analysis of purchasing approaches associated to CSR strategies presenting drivers and benefits for MNCs to use local suppliers. Globalization and the pressure for better products and lower costs leveraged international companies in terms of sourcing decisions. Choosing key capabilities and sourcing locations suddenly became a fundamental strategic decision. Many MNCs have chosen to use Local Sourcing as a differential and a platform to create value to both the company and the society - while enabling companies to strengthen their market position, source quality raw materials at fair prices, the relationship with those suppliers brought economic and social progress to underdeveloped communities. Studies on local sourcing widely focus on the competitive advantages that companies may attain, and value chain models that can be tailored to fit their global business strategy, however there is limited knowledge on the creation of shared value. Therefore the purpose of this research was to identify aspects of corporate strategy, supplier management and collaboration that influenced the creation of shared value. A qualitative exploratory case study was conducted, evaluating two specific business cases, to examine the strategies and initiatives that had as basis the relationships with local suppliers. The research was separated in three steps to identify (1) influences of sourcing decisions, (2) aspects that make supplier management successful and (3) value created by the outcome of this decisions. Theoretical concepts of CSR, SCM, Collaboration and Shared Value were used to support the results and main findings. The outcome of this investigations revealed that the idea of co-creation of value is inserted in corporate culture and it is a driver for MNCs to use local suppliers, though having it embedded in its strategy does not guarantee that shared value will be create. More than that, many components of a CSR purchasing strategies and relationships characteristics must be adjusted to generate transformational changes and that elements of collaboration such as transparency and independence are vital to enhance commitment between the MNC and the local business and create value.